Miniaturized, rapid separation of neodymium from ultramafic and chondritic samples prior to high precision measurements of 142, 143Nd/144Nd isotope ratios by TIMS. Issue 10 (12th September 2019) - Pin, Christian; Gannoun, Abdelmouhcine
Abstract : An improved method is described for isolating Nd from challenging silicate materials. This scheme does not involve evaporation steps and can be performed in about 12 hours, allowing the separation of Nd from Sm, Ce and Pr with good yields. Abstract : An improved method is described for isolating Nd from challenging silicate materials. After a short dissolution with hydrofluoric acid, the 1–2 gram sample is subjected to a protracted treatment with nitric and hydrochloric acid at mild temperature. Then, the sample is taken up in 15–20 mL of 1 M HNO3 . Residual fluorides are isolated by centrifugation, and decomposed with boric acid. Ascorbic acid is added to reduce Fe(iii ) to Fe(ii ) and the solution is loaded onto a small column containing 1.5 mL of TRU extraction chromatography (EXC) resin, to extract the REE + Th and U. The LREEs are stripped by using 3 M HCl and directly loaded onto the next, on-line column filled with 1 mL of DGA EXC resin which achieves the separation of Nd from Sm, and from the bulk of Ce and Pr. Neodymium is stripped with 0.006 M HCl onto a 1 mL column of LN2 EXC resin for further purification from residual Ce and Pr. By virtue of small EXC columns and reagents permitting direct cross-over from a column to the next one, this scheme does not involve evaporation steps, and can be performed in about 12 hours, with good Nd yields and negligible blanks. The method is validated by the analysis of depleted basic and ultra-basic rocks, and a sample of the Allende carbonaceous chondrite. Compared with previous methods used to process difficult samples, this protocol is drastically down-scaled, relatively simple to implement, and much less demanding in terms of analyst time, reagent volumes, and costs.